The Use of external control in training and educational management system in a higher military educational establishment - Osypenko, S. N.; Starodubtsev, S. A. (Honor and Law, 2019)
The article deals with organizational and methodological recommendations for external control of correspondence the level of graduates’ of higher military educational establishments to their sevice appointment and the application of its results in management of training and educational process.